Inspeksi Teknis Boiler: Analisis Kelayakan Operasional Berdasarkan Pengujian Non-Destruktif - Nurul Laili Arifin; Muhammad Alief Anderson; Ninda Hardina Batubara Arifin; Roza puspita; Nurul Ulfah; Ari Wibowo; Nugroho Pratomo Ariyanto; Muhammad Ismail (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2026)
Riksa Uji is a technical inspection process performed on steam equipment to assess operational feasibility, detect potential damage, and ensure compliance with occupational safety standards. This study focuses on a fire-tube boiler unit operated by an industrial company. The objective is to confirm that the boiler remains in a safe operational condition. Methods used include document review, visual inspection, dimensional measurements, and several tests such as Magnetic Particle Inspection (MPI), hydro test, steam test, and evaluation of the electrical safety system. The boiler was found to have a design pressure of 16 bar, working pressure of 15 bar, and a capacity of 1600 kg/h (32,600 liters). MPI results showed no physical defects or issues in safety components. The hydro test, performed at 18 bar for 30 minutes, revealed no leaks or structural failure. Steam testing confirmed that both safety valves operated below the set pressure of 17 bar. Electrical safety tests indicated that all protection systems functioned properly. Based on the results of all inspection stages, the boiler meets technical requirements and is declared safe for continued use. This study emphasizes the importance of regular inspections to maintain equipment reliability and ensure workplace safety.